Impact of web and digital experience on the stickiness of third party hotel website / Nina Farisha Isa...[et al] - Nina Farisha, Isa; Nor Adila, Rosli; Fairuz, Hakim; Irina, Mohd Akhir (Faculty of Hotel Management and Tourism, Universiti Teknologi MARA Selangor, Puncak Alam Campus, 2017)
The rapid development and use of mobile technologies has changed the way of our everyday lives, especially individual that feel a sense of experience as a tool for enhancing task performance. In addition, mobile technologies also have changed the way marketers and consumers communicate. However, digital experience is still a largely unexplored concept in both hospitality research and practice. Drawing from the literature on human computer interaction in information system and flow theory in consumer behavior research, this study theoretically identifies and empirically explores the concept of flow through experience and its antecedents (i.e., web experience and digital experience on the outcome, and web stickiness) in the hotel context. Using eCommerce website and mobile technologies as the target, an offline and online survey will be conducted. This study contributes theoretically and empirically to the body of IS use research and has managerial implications, suggesting that web experience and digital experience is a necessary condition for stick to the websites. As a result, by improving user’s experience through digital applications is critical to build strong relationships with the consumers.